2008
DOI: 10.1111/j.1365-2702.2007.02040.x
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of barriers to and facilitators of research utilization in Iranian nursing

Abstract: Key factors that need attention in implementing research results into practice are suggested. Clearly, identification of barriers and facilitators is useful potentially to overcome barriers and enforce facilitators and this could ultimately improve nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
110
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(135 citation statements)
references
References 40 publications
19
110
2
4
Order By: Relevance
“…The lack of adequate resources and physical facilities for EBP are universal and our finding is consistent with previous research [7,8,17,21,24,26]. In a qualitative study in Latin American hospitals, professional informants reported scarce physical facilities as their main hurdle to change perinatal care practice [21].…”
Section: Organizational/system-based Barriers To Ebpsupporting
confidence: 82%
See 2 more Smart Citations
“…The lack of adequate resources and physical facilities for EBP are universal and our finding is consistent with previous research [7,8,17,21,24,26]. In a qualitative study in Latin American hospitals, professional informants reported scarce physical facilities as their main hurdle to change perinatal care practice [21].…”
Section: Organizational/system-based Barriers To Ebpsupporting
confidence: 82%
“…They stated lack of free time and hectic workload, consistent with other authors from Africa [6,7,10,29] and elsewhere [4,5,8,17,18]. These hurdles can deter staff from attending a journal club, searching for articles, reading or integrating research evidence into practice.…”
Section: Organizational/system-based Barriers To Ebpsupporting
confidence: 48%
See 1 more Smart Citation
“…42 Nursing shortage is a serious issue in many Asian countries such as Iran; and nurses are practicing under an overwhelming workload. 43,44 This issue results in less nurses being available for patients, and the resulting time restriction dissuade the nurses from providing the education for their patients. 45 In addition to the unbalanced nursepatient ratio due to nurse shortage and large number of hospitalized patients, nurses are expected to do nonprofessional tasks such as coordinating, transporting patients and performing ancillary services which leading to increased workload.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing is the largest healthcare profession in Iran responsible for the care of patients (16). Road traffic accidents are considered to be the second cause of mortality in Iran (first cause being coronary heart disease).…”
Section: Background In Iranmentioning
confidence: 99%